الكشف عن وجود بيوض ديدان طفيلية في مياه خزان سد الصوراني في محافظة طرطوس - ديوب, أمل; التميمي, كنعان; مظلوم, مرفت (Latakia University Journal -Biological Sciences Series, 2019)
The study was conducted on samples of Al-Sourani dam reservoir water (Al- Sheikh Badr - Tartous province) for proving or denying the presence of parasitic helminthes eggs during the period from October 2015 to September 2016. The study samples were collected from the beginning, middle and the end of the dam reservoir. The study showed presence of parasitic helminthes eggs: Ascaris lumbricoides, Taenia saginata, and Hymenolepis nana. The total prevalence was 1.57 egg / liter. Taenia saginata eggs were the most common, followed by the eggs of the Ascaris, and then the eggs of the Hymenolepis nana, especially in the Summer and Autumn. Our study is the first to investigate parasitic helminthes eggs in AL-Sourani dam reservoir water. أجريت الدراسة لعينات من ماء خزان سد الصوراني (الشيخ بدر – محافظة طرطوس) بهدف اثبات أو نفي وجود بيوض ديدان طفيلية، خلال الفترة الممتدة من تشرين الأول 2015 ولغاية أيلول 2016. جمعت عينات الدراسة من بداية خزان السد، ومخرجه ومنتصفه بمعدل عينة (10) لتر شهرياً . أظهرت الدراسة وجود بيوض لديدان طفيلية هي: بيضة الاسكاريس(الصفر الخراطيني)Ascaris lumbricoides ، و الشريطية العزلاء Taenia saginata، والمحرشفة القزمة Hymenolepis nana. وكانت نسبة الانتشار الكلي بمعدل 1.57 بيضة /لتر. كانت بيوض الشريطية العزلاء هي الأكثر انتشاراً، تلتها بيوض الاسكاريس، ثم بيوض المحرشفة القزمة خصوصاً في فصلي الصيف والخريف. تعد دراستنا هي الأولى التي أجريت تحرياً عن بيوض ديدان طفيلية في مياه خزان سد الصوراني .